2018
DOI: 10.1111/1365-2745.13068
|View full text |Cite
|
Sign up to set email alerts
|

Inbreeding diminishes herbivore‐induced metabolic responses in native and invasive plant populations

Abstract: Inbreeding and herbivory can interactively reduce the performance of flowering plants. Here, we investigated whether the magnitude of plant inbreeding depression increases under herbivory as a result of diminished leaf metabolic responses to herbivory in inbreds, which entails increased herbivore growth and feeding damage. We additionally explored whether genetic differentiation among native and invasive plant populations impacts the magnitude and direction of these inbreeding × herbivory interactions. Inbred … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 61 publications
3
19
1
Order By: Relevance
“…Overall invasive plants received more infestation damage, but exhibited similar or even higher values for fitness-related traits as native plants (Table 1). This observation has also been made in previous studies on S. latifolia (Blair & Wolfe, 2004;Schrieber et al, 2018Wolfe et al, 2004) and suggests that invasive populations evolved increased tolerance of enemy infestation. The evolution of increased tolerance during range expansion has been observed in several other plant species (Abhilasha & Joshi, 2009;Zou, Rogers, & Siemann, 2007) and is assumed to arise from shifts in the natural enemy community, that is, reduced attack by specialists and increased attack by generalist (Fornoni, 2011).…”
Section: Have I × E Interactions Contributed To Invasion Success Insupporting
confidence: 85%
See 3 more Smart Citations
“…Overall invasive plants received more infestation damage, but exhibited similar or even higher values for fitness-related traits as native plants (Table 1). This observation has also been made in previous studies on S. latifolia (Blair & Wolfe, 2004;Schrieber et al, 2018Wolfe et al, 2004) and suggests that invasive populations evolved increased tolerance of enemy infestation. The evolution of increased tolerance during range expansion has been observed in several other plant species (Abhilasha & Joshi, 2009;Zou, Rogers, & Siemann, 2007) and is assumed to arise from shifts in the natural enemy community, that is, reduced attack by specialists and increased attack by generalist (Fornoni, 2011).…”
Section: Have I × E Interactions Contributed To Invasion Success Insupporting
confidence: 85%
“…. latifolia populations investigated in the present study,Schrieber et al (2018) demonstrated that inbreeding significantly compromises the plants' metabolic responses to insect herbivory. This study also indicated that higher infestation damage on inbred S. latifolia individuals can result from compensatory feeding triggered by poor host plant quality.…”
mentioning
confidence: 54%
See 2 more Smart Citations
“…In addition, individual extracts of leaf material in the same composition as used in the bioassays, i.e., leaf material pooled from all plants per chemotype, and fractions of extracts from leaf material pooled from all plants including both chemotypes, were prepared. Samples were extracted in 90% methanol and chemical analysis was performed according to Schrieber et al (2019) 57 , but in negative electrospray ionisation mode and with further modifications of instrument settings and in processing raw data from chromatograms (see Supplementary Information Methods S3). UV absorption was recorded at 360 nm.…”
Section: Methodsmentioning
confidence: 99%